Assessment of Neurocognitive Functions, Olfaction, Taste, Mental, and Psychosocial Health in COVID-19 in Adults: Recommendations for Harmonization of Research and Implications for Clinical Practice. (9th July 2022) - Cysique, Lucette A.; Łojek, Emilia; Cheung, Theodore Ching-Kong; Cullen, Breda; Egbert, Anna Rita; Evans, Jonathan; Garolera, Maite; Gawron, Natalia; Gouse, Hetta; Hansen, Karolina; Holas, Paweł; Hyniewska, Sylwia; et al.
Abstract: Objective: To propose a set of internationally harmonized procedures and methods for assessing neurocognitive functions, smell, taste, mental, and psychosocial health, and other factors in adults formally diagnosed with COVID-19 (confirmed as SARS-CoV-2 + WHO definition). Methods: We formed an international and cross-disciplinary NeuroCOVID Neuropsychology Taskforce in April 2020. Seven criteria were used to guide the selection of the recommendations' methods and procedures: (i) Relevance to all COVID-19 illness stages and longitudinal study design; (ii) Standard, cross-culturally valid or widely available instruments; (iii) Coverage of both direct and indirect causes of COVID-19-associated neurological and psychiatric symptoms; (iv) Control of factors specifically pertinent to COVID-19 that may affect neuropsychological performance; (v) Flexibility of administration (telehealth, computerized, remote/online, face to face); (vi) Harmonization for facilitating international research; (vii) Ease of translation to clinical practice. Results: The three proposed levels of harmonization include a screening strategy with telehealth option, a medium-size computerized assessment with an online/remote option, and a comprehensive evaluation with flexible administration. The context in which each harmonization level might be used is described. Issues of assessment timelines, guidance for home/remote assessment to support data fidelity and telehealth considerations, cross-cultural adequacy, norms, and impairment definitions are also described. Conclusions: The proposed recommendations provide rationale and methodological guidance for neuropsychological research studies and clinical assessment in adults with COVID-19. We expect that the use of the recommendations will facilitate data harmonization and global research. Research implementing the recommendations will be crucial to determine their acceptability, usability, and validity.